Rapid, Isothermal DNA Self‐Replication Induced by a Destabilizing Lesion1. Issue 40 (6th August 2013) - Kausar, Abu; Mitran, Catherine J.; Li, Yimeng; Gibbs‐Davis, Julianne M.
<x xml:space="preserve">Abstract</x> You spin me round: Using a destabilizing abasic site and high concentration of ligase, rapid DNA self‐replication in an isothermal ligase chain reaction (LCR) was produced. Both destabilization and rapid ligation are essential for proper LCR replication. This method also provides insight into prebiotic nucleotide replication and is a potential amplification method for biodiagnostics.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>